Strategi Kyai dalam Membimbing Santri Menghadapi Media Digital Berbasis Hadits Akhlak - Fathur Rohman; Nasrulloh (Al-Kindi, 2026)
This research discusses the role and strategy of kyai in guiding students to face digital media challenges by using moral hadith as an ethical foundation. Pesantren are currently faced with changes in the behavior of students due to wide access to information, unlimited communication patterns, and the ease of obtaining content that is not in harmony with Islamic moral values. Through a qualitative approach based on content analysis, this study examines pesantren leadership literature, digital morals, and relevant hadiths. The results of the study show that kyai plays a central role as a spiritual guide, a supervisor of digital behavior, as well as an exemplary figure in responding to the flow of information. The coaching strategies found include supervision of the use of gadgets, habituation of manners through example, and the integration of hadiths such as